Avaliação da simulação de efeitos unilaterais de concentrações horizontais: uma aplicação do modelo PC-AIDS - Cardoso, Marcelo José Ranieri (2006)
It´s consensus that in antitrust analysis that the concentration act taken by firms with significant market share must to go through some investigation in due to its approval, because of harmful effects that it might bring to the competition on industry. Competition is always desirable for the benefits that it generates in the economical welfare. Under the light of the economic investigations that the competition policy system performs, this work analyzes the measures of simulations of unilateral effects of horizontal concentrations. The evaluations carried out here test the use of PC-AIDS model (Proportionaly Calibrated AIDS) from Epstein and Rubinfeld (2002). Among some of the conclusions extracted from the use of this model we have: (i) for markets with low economic concentration, the model evaluated for a confidence interval of estimated own-price elasticities shows robust measures, and (ii) for markets with high economic concentration, more attention must be paid for the correlation between calibrated and estimated values of own-price elasticities, in order to ensure that will not occur an under or overestimation of unilateral effects of concentration acts. This result is analyzed in Nestlé/Garoto’s case.